ابراہیمی مذاہب میں خواتین کی تفسیری جدوجہد: علمی احیاء، مذہبی اختیار اور صنفی مساوات کا تقابلی جائزہ: Women's Interpretive Struggles in Abrahamic Religions: A Comparative Study of Scholarly Revival, Religious Authority, and Gender Equality (Al-Qamar, 2025)
This research paper examines the complex and interconnected relationship between modern women and the interpretation of sacred texts in the three major Abrahamic religions Judaism, Christianity, and Islam. In light of the extensive scholarly literature, this study discusses the historical reality that women have long been excluded from the role of interpreters of religious texts. It also provides a detailed examination of the rise of feminist hermeneutics, contemporary debates and controversies, comparative aspects of different religious traditions, and the challenges and opportunities facing women scholars and religious leaders in the modern era.The research analysis makes it clear that although women’s exclusion from the process of interpretation is deeply rooted in history, modern feminist movements in all three traditions are adopting a common scholarly approach to rediscovering the meanings of sacred texts, centralizing marginalized voices, and challenging male or patriarchal readings.This paper argues that the reinterpretation and reinterpretation of sacred texts from a feminine perspective is not merely an academic exercise, but a comprehensive and transformative process that plays a fundamental role in reshaping religious authority, religious practice, and gender relations within Abrahamic faith communities.
Keywords: Feminist theology, hermeneutics, Abrahamic religions, sacred texts, women's interpretation, Judaism, Christianity, Islam, gender studies, religious feminism